The issue of developing hospitality as a component of entrepreneurial potential for the tourism industry of Ukraine - Liubchuk Оlga; Yarchenko, Yuliia (Management and Entrepreneurship: Trends of Development, 2019)
The paper is aimed at elucidating the components of entrepreneurial potential and considering hospitality as a constituent of the modern entrepreneur’s personal resource in tourism industry. In the study, the following methods were used: a method of theoretical analysis, comparative analysis, diagnostic techniques, in particular the technique of “Investigation of the person’s entrepreneurial potential”, quantitative methods of data processing, qualitative analysis of the results obtained. Based on the approach developed by the G.S. Kostiuk Institute of Psychology of the National Academy of Educational Sciences of Ukraine, the personality components of entrepreneurial potential are as follows: orientation to entrepreneurial activity, certain intellectual, emotional and volitional, communicative, business qualities as well as internality. Hospitality as a personality component of entrepreneurial potential represents a characteristic feature of a successful entrepreneur in the service sector of Ukraine. A comparative analysis of entrepreneurial and managerial potentials’ components revealed a need for developing business as well as emotional and volitional qualities of entrepreneurs. Development of entrepreneurs’ business qualities requires conducting behavioral and communicative trainings and attending classes at the School of Leadership. As a coclusion, the paper clearly defines hospitality as a personality component of entrepreneurial potential for successful performance in the service sector. Such knowledge will assist in developing the Ukrainian tourism industry in line with the global trends, given the national and mental features of the hospitality of Ukrainians. JEL Classification: L29, L83, M14, O15